2016
DOI: 10.1074/jbc.m116.743906
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Facilitates Latent HIV Reactivation through Maintaining the Function of Positive Transcriptional Elongation Factor b (p-TEFb) under Proteasome Inhibition

Abstract: Edited by George DeMartinoThe persistence of HIV in resting memory CD4؉ T cells at a latent state is considered as the major barrier on the path to achieve a cure for HIV. Proteasome inhibitors (PIs) were previously reported as latency reversing agents (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Heat shock protein 90 (Hsp90) is a molecular chaperone that is required for the normal functioning of a number of client proteins, and recent studies have demonstrated that Hsp90 activity is required for reversal of HIV latency (29)(30)(31)(32)(33). Additional work has also shown that Hsp90 deacetylation by a class 2 HDAC, HDAC6, activates Hsp90 activity (34,35) and that vorinostat, which inhibits HDAC6, causes acetylation of Hsp90 and inhibits its function (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Heat shock protein 90 (Hsp90) is a molecular chaperone that is required for the normal functioning of a number of client proteins, and recent studies have demonstrated that Hsp90 activity is required for reversal of HIV latency (29)(30)(31)(32)(33). Additional work has also shown that Hsp90 deacetylation by a class 2 HDAC, HDAC6, activates Hsp90 activity (34,35) and that vorinostat, which inhibits HDAC6, causes acetylation of Hsp90 and inhibits its function (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…While differences in HSP90 protein expression were not observed, it is still possible that a deficiency in HSP90 activity under hypothermic conditions is responsible for the observations we described. HSP90 has been shown to be a positive regulator of HIV gene expression in numerous studies (26)(27)(28)(29)(30)(31)(32)(33)(34), and the mechanism of this activity is likely pleiotropic. Our findings further implicate HSP90 as potentially playing an important role in regulating HIV-1 latency, drawing a novel connection between quiescence-induced latency and HSP90 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature supports the role of HSP90 in regulating HIV-1 gene expression, and the mechanisms of this effect are likely pleiotropic. HSP90 has been implicated in the activation of the NF-B pathway (25), the formation of stable P-TEFb complexes (26,27), and the formation of RNA polymerase II (Pol II) complexes in the cytoplasm (28). Hyperthermia has been shown to increase HIV-1 gene expression in persistently infected cell lines, in an HSP90-dependent manner, increasing the colocalization of HSP90 with the HIV-1 promoter (29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Moreover, when added to cells together with entinostat, SAHA and RMD reduced GFP reporter expression (19). A specific inhibitory mechanism was proposed for the case of SAHA, which may interfere with HIV expression via inhibition of HDAC6, thus causing changes in the acetylation state of its nonhistone targets, such as chaperone protein HSP90 (19), which is required for reversal of HIV latency (35)(36)(37). This mechanism of inhibition, however, would not be an expected mechanism for RMD, because it does not inhibit HDAC6.…”
Section: Secondary Mechanisms Of Action Of Hdaci and Hiv Latencymentioning
confidence: 99%